Analysis of Competitiveness and Factors Affecting the Level of Potato Export to Singapore and Malaysia - Desi Nurfiana Fauziah; - Riniati; Sunlip Wibisono (Trunojoyo University of Madura, 2021)
This study purpose to analyze competitiveness and the factors that influence the level of Indonesian potato exports in Singapore and Malaysia. The analytical method used in this study is the quantitative Revealed Comparative Advantage (RCA) method, Export Product Dynamic (EPD), and OLS analysis. The destination countries for potato exports in Indonesia are Singapore and Malaysia. This study uses annual time series data from 1989 to 2018. The results of the RCA analysis show that Indonesian potatoes have strong competitiveness in Singapore in 1999-2017, although in 1999-2003 the value of Singapore RCA was inferior to Malaysia. Whereas in Malaysia, Indonesian potatoes have strong competitiveness only in 1999-2006. The results of analysis of Indonesian potato EPD on the Singapore market are in a retreat position and Malaysia is in a lost opportunityposition. The results of OLS analysis in both countries show that the variable that has a significant effect on the level of potato exports is the GDP of the destination country and the real exchange rate. While the price of exports only affects Singapore. This study purpose to analyze competitiveness and the factors that influence the level of Indonesian potato exports in Singapore and Malaysia. The analytical method used in this study is the quantitative Revealed Comparative Advantage (RCA) method, Export Product Dynamic (EPD), and OLS analysis. The destination countries for potato exports in Indonesia are Singapore and Malaysia. This study uses annual time series data from 1989 to 2018. The results of the RCA analysis show that Indonesian potatoes have strong competitiveness in Singapore in 1999-2017, although in 1999-2003 the value of Singapore RCA was inferior to Malaysia. Whereas in Malaysia, Indonesian potatoes have strong competitiveness only in 1999-2006. The results of analysis of Indonesian potato EPD on the Singapore market are in a retreat position and Malaysia is in a lost opportunity position. The results of OLS analysis in both countries show that the variable that has a significant effect on the level of potato exports is the GDP of the destination country and the real exchange rate. While the price of exports only affects Singapore.